THE LIFESTYLE OF A MODERN GIRL AS A FACTOR DETERMINING REPRODUCTIVE POTENTIAL - Карина Ниловна Мингареева; Альфия Галимовна Ящук; Ксения Николаевна Ящук (Мать и дитя в Кузбассе)
The aim of the research – to give a quantitative assessment of the influence of lifestyle components on the reproductive potential of female students for scientific substantiation of the priority of measures for the formation of a healthy lifestyle.